Comparative Study of Psoriasis and Atopic Dermatitis - Mohan, Fatima Rashid (Journal of medical and pharmaceutical sciences, 2025)
This comprehensive comparative study aims to elucidate the distinctive and overlapping aspects of psoriasis and atopic dermatitis. These two prevalent chronic inflammatory skin diseases substantially impact global health. Employing a systematic literature review of peer-reviewed articles, clinical trials, and meta-analyses from 2010 to 2024, the research synthesises current evidence on epidemiology, pathophysiology, clinical manifestations, comorbidities, disease burden, and management approaches. Key findings highlight that while both conditions share immune dysregulation and impaired skin barrier function, psoriasis is primarily driven by the IL-23/Th17 axis with characteristic scaly plaques and significant cardiovascular and musculoskeletal comorbidities. In contrast, atopic dermatitis stems from filaggrin deficiency and Th2-biased immunity, presenting with pruritic, lichenified lesions and frequent atopic comorbidities such as asthma and allergies. Both diseases profoundly diminish quality of life through physical symptoms and psychological distress. The study emphasises the necessity of accurate differential diagnosis and advocates for patient-centred, multidisciplinary care strategies that encompass personalised therapeutic plans, psychosocial support, and education to manage these lifelong conditions effectively. Recommendations call for increased public awareness, enhanced diagnostic precision, comprehensive management incorporating mental health, and equitable access to advanced biologic treatments to improve patient outcomes and reduce systemic disease burden.